2018
DOI: 10.6090/jarq.52.115
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Product Authenticity and Geographical Origin Traceability

Abstract: As the security of agricultural products has become a serious issue faced by people worldwide in recent decades, measures for an effective supervision system for agricultural product quality and safety are continuously being developed. In such a system, the assessment of agricultural product authenticity and geographical origin traceability could play a very important role. Recently, researchers have been focusing on some successful techniques, including the stable isotopic technique, compositional analysis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that the NIR plateau between 800 nm and 1300 nm, as well as water absorption bands above 1300 nm, are common characteristics of reflectance spectra of all healthy green plants. The high reflectivity in the NIR region of 800 nm to 1300 nm is due to the porous plant leaf structure (tissues and cells), whereas the low reflectivity above 1300 nm is caused by water absorption [3,39]. The 1300 nm wavelength is the dividing line of the histological structures and the specific components of plant leaves, both of which are the main factors affecting the reflectance spectral characteristics of the leaves.…”
Section: Characteristic Wavelength Bandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the NIR plateau between 800 nm and 1300 nm, as well as water absorption bands above 1300 nm, are common characteristics of reflectance spectra of all healthy green plants. The high reflectivity in the NIR region of 800 nm to 1300 nm is due to the porous plant leaf structure (tissues and cells), whereas the low reflectivity above 1300 nm is caused by water absorption [3,39]. The 1300 nm wavelength is the dividing line of the histological structures and the specific components of plant leaves, both of which are the main factors affecting the reflectance spectral characteristics of the leaves.…”
Section: Characteristic Wavelength Bandsmentioning
confidence: 99%
“…In recent decades, with the advancements in spectroscopy and imaging technologies, hyperspectral imaging (HSI) technology has emerged as a highly efficient nondestructive measurement method. This technology was originally developed for remote sensing and is widely used in resource management, agriculture, mineral exploration, and environmental monitoring [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that the traceability system of agricultural products based on blockchain and IoT can improve the efficiency and reduce the logistics cost to a certain extent. "Blockchain + Internet of Things" realizes the risk-free, leverage-free and high-efficiency transfer of credit between things, and realizes the unification of capital flow, logistics and information flow on the chain [38]. The application of IoT ensures the trustworthiness of everything, realizes the mapping between the physical world and the digital world, and ensures the authenticity and integrity of the information on the chain, and further helps the traceability development of the smart supply chain.…”
Section: * Self-generated By the Authormentioning
confidence: 99%
“…All methods for food authenticity developed thus far have no more than one partial use for practical application as an analysis guideline. For both measuring the products and determining the production environment (e.g., soil conditions), a non-destructive system has been developed (Zhao & Nakano 2018). An environmental measurement node using open source hardware (UECS: Ubiquitous environmental control system) has also been developed (Yasuba et al 2013).…”
Section: Food Safety Combining Analytical Chemistry and Information Cmentioning
confidence: 99%